Production and Financial Management Training to Increase Micro-Business Productivity in Rural Areas - Bella Suci Novitri; Walla Astianty Putri; Joko Rianto (Indonesia Journal of Engineering and Education Technology (IJEET), 2025)
This study aims to analyze the determinants of financial distress in manufacturing companies in Indonesia using the Altman Z-Score Model as an analytical framework from a qualitative perspective. Financial distress is understood as a phase of declining financial performance characterized by a weakening company's ability to meet short-term and long-term obligations. This study employed a qualitative approach with a multiple case study design on several manufacturing companies indicated as experiencing financial distress based on the Altman Z-Score classification. Data were collected through a documentary study of financial statements, annual reports, and in-depth interviews with management and financial analysts. Data analysis techniques included data reduction, thematic categorization, and inductive conclusion drawing to identify patterns of financial distress determinants. The results indicate that the determinants of financial distress are influenced not only by financial ratios such as liquidity, profitability, and leverage, as reflected in the Altman Z-Score components, but also by non-financial factors such as the quality of corporate governance, the effectiveness of managerial strategies, reliance on short-term debt, and the dynamics of industry conditions. These findings confirm that the Altman Z-Score model is effective as an early detection tool, but its interpretation needs to be enriched with contextual and managerial analysis to obtain a comprehensive picture of a company's financial health. This research provides theoretical contributions to the development of qualitative-based financial distress studies, as well as practical implications for management in formulating risk mitigation strategies and sustainable financial restructuring.